Reception Dynamics and the Theme of Human Fall in Absurdist Literature: An Interactive Reading of Three Short Stories by Friedrich Dürrenmatt - Hamad, Hani Khamis (Journal of Humanities & Social Sciences, 2025)
This study explores the reception dynamics of narrative structure in three short stories by Friedrich Dürrenmatt.—The Eclipse, The Fall, and The Winter War in Tibet—within an interpretive framework based on the hypothesis that these texts narratively embody the concept of "human downfall" in an absurdist context marked by the semantic collapse, and the fragmentation of the self.The research adopts a qualitative, interpretive methodology grounded in Wolfgang Iser’s theory of gaps of reception (1978). A reader-response session was conducted with five participants from diverse professional and cultural backgrounds. Data were collected through direct transcription of participants' interpretive reflections and analyzed thematically within an existential-absurdist framework, drawing on both Western and Arabic critical literature.Findings revealed that the notion of "downfall" was not perceived as a fixed or closed concept, but as an open semantic structure whose meanings shift according to each reader’s context, emotional resonance, and cultural background. The study also identified a rich interpretive engagement encompassing psychological, social, epistemological, and existential dimensions, highlighting the reader’s active role in reconstructing meaning within absurdist narratives.The study concludes that employing an interactive qualitative approach informed by reception theory offers an effective pathway for analyzing absurd literature. It calls for the development of contemporary Arab critical approaches that account for the plurality of reading horizons, and recommends integrating qualitative interpretation with broader quantitative tools to further investigate the cultural dynamics of literary understanding.
Keywords: absurd literature; human downfall; reception theory; qualitative analysis; interpretation; Dürrenmatt; reader response